Biodesalination using halophytic cyanobacterium Phormidium keutzingianum from brackish to the hypersaline water. (November 2022) - Zafar, Abdul Mannan; Javed, Muhammad Asad; Aly Hassan, Ashraf; Sahle-Demessie, Endalkachew; Harmon, Stephen
Abstract: The biodesalination potential at different levels of salinity of Phormidium keutzingianum ( P. keutzingianum ) was investigated. A wide range of salinity from brackish to hypersaline water was explored in this study to ensure the adaptability of P. keutzingianum in extreme stress conditions. Brackish to hypersaline salt solutions were tested at selected NaCl concentrations 10, 30, 50, and 70 g.L −1 . Chloride, pH, nitrate, and phosphate were the main parameters measured throughout the duration of the experiment. Biomass growth estimation revealed that the studied strain is adaptable to all the salinities inoculated. During the first growth phase (till day 20), chloride ion was removed up to 43.52% and 45.69% in 10 and 30 g.L −1 of salinity, respectively. Fourier transform infrared spectrometry analysis performed on P. keutzingianum showed the presence of active functional groups at all salinity levels, which resulted in biosorption leading to the bioaccumulation process. Samples for scanning electron microscopy (SEM) analysis supported with electron dispersive X-ray spectroscopy analysis (EDS) showed NaCl on samples already on day 0. This ensures the occurrence of the biosorption process. SEM-EDS results on 10th d showed evidence of additional ions deposited on the outer surface of P. keutzingianum. Calcium, magnesium, potassium, sodium, chloride, phosphorus, and iron were indicated in SEM-EDS analysis proving the occurrence of the biomineralization process. These findings confirmed that P. keutzingianum showed biomass production, biosorption, bioaccumulation, and biomineralization in all salinities; hence, the strain affirms the biodesalination process. Graphical abstract: Image 1 Highlights: Salt removal happens with both biosorption and bioaccumulation process. Chloride ions were reduced up to 40–45% within the first phase of growth for 10 & 30 g/L. FTIR analysis corroborated the presence of bonds that adsorb Na + and Cl − ions. SEM-EDS analysis confirmed the biomineralization process occurring in P. keutzingianum .